Christmas Eve at the Mellops' - Ungerer, Tomi, 1931- (Phaidon, 2011)
It is the day before Christmas. The four Mellops brothers all have the same idea - to surprise their family with a Christmas tree. By Christmas Eve the hall is full of trees - and tears - and the Mellops must find a way to share the festive cheer.